A retrospectiva dos direitos da criança e do adolescente : uma análise crítica perante a mídia conservadora - Menezes, Anne Cristian Estevem de (2016)
The present study seeks to present a critical analysis of the rights of children and adolescents before and the conservative media, through legal, normative, historical and conceptual aspects about the children and youth public. From this perspective, the historicity of childhood and adolescence will be addressed at the national and global levels, through laws and newspapers that highlight this theme, analyzing critically the mass media used in different periods of this history. The subject under study is linked to the research line "Social Service and Social Policies", one of the axes of the Postgraduate Program of the Faculty of Social Service of the School of Humanity of PUCRS. The approach of the theme refers to the discussion of the Irregular Situation Doctrine and the Doctrine of Integral Protection, since there are different conceptions, both in the law and in the defense of children and adolescents, as well as in the protection system. The research investigates the changes of conception on the Rights of the Child and Adolescents that are expressed in the Brazilian legislation and in official documents, from 1988 to 2015. In this process of investigation, the Critical Dialectic method was used to unravel reality. For this, we sought, through historicity and contradictions, to reach the social totality; Recognizing it, however, in its dynamic, unfinished and constantly changing movement. These constant transformations become visible in the analysis of this research, when the social policies in Brazil and the conception of the rights of children and adolescents, regulated by both the Statute of the Child and the Adolescent, as well as other social legislation and policies are addressed. It is understood that these constant transformations are also influenced and manifested through the social movements of the child and juvenile population and their processes of struggle and resistance, for the guarantee and the realization of their rights. Initially, it was sought to delimit the universe of research in Brazilian legislation, in official publications and in newspapers dating from 1988, contemplating in the research the period from 1988 to 2015. However, this period was broadened, going from 1979 to 2015 , Considering the need to understand the legal changes introduced in 1979. However, the focus of these changes began in 1988, with the publication of the new Federal Constitution and the conceptual changes on child and adolescent protection, brought and established by the Magna Carta . The sampling of this research takes place with the published legislation from 1979 to 2015 and with the reports and researches on the subjects: institutional reception (shelters); Children and adolescents (children and adolescents); Law, and Juvenile Justice and Juvenile Court (Juvenile Court - before 1989). The search for journalistic data used a universe that covers the period from 1979 to 2015. The keywords searched in the journalistic data were: "juveniles", Juvenile Court, Juvenile Court and Youth, childhood and youth, children's rights and Adolescents, shelter, institutional shelter, protection of children and adolescents and measures of protection. The research sample was characterized as non-probabilistic and intentional, aiming at knowing the conception expressed in official documents about the rights of children and adolescents in all spheres of government. The sample focuses on 275 reports between the years 1999 to 2015, in which thematic axes were categorized as: rights of children and adolescents, family and community coexistence, shelter / institutional reception, affective adoption / sponsorship, public policies, violation of rights , Life history, urban violence, violence against children and adolescents, and criminal age. However, emphasis was placed only on the first three axes. The total universe of journalistic material is found in 319 reports, however, due to the lack of some data from other years, it was decided to reduce the sample to 275 reports. The reports of the year 1979 were used to better visualize the themes and forms of manifestation of newspapers at the time. The research stages consisted, first of all, in the survey and selection of the materials to be analyzed, taking into account that the previously established criteria contemplate the objectives and purpose of the research. In the second stage, the material is read and the categories highlighted as relevant, taking into account the period and historical context in which they were produced. As for the third stage, data collection was performed through the technique of documentary analysis and data interpretation, based on content analysis (Bardin, 1977). The data were analyzed through the coding, classification and categorization procedures, resulting in reference frames that will serve as the basis for the realization of the inferences.Nevertheless, the explanatory categories found to better understand the installed reality are articulated and referenced in a conjuncture around the theme: children's and adolescents' rights, social policies - Social Assistance and the media. Nevertheless, for a better interpretation and analysis of this study, the methodology used to analyze the social theory of mass communication was used John Thompson (1995), in the face of interpretation methodology. Firstly, it refers to socio-historical analysis, in which the social and historical conditions of production, circulation and reception of symbolic forms, as well as contextualized social phenomena (empirical, observational and documentary methods) will be analyzed. Subsequently, the methodology of interpretation, stands out the analysis, formal or discursive, which means to analyze the symbolic forms and their complex construction. And finally the interpretation methodology includes the interpretation and reinterpretation of the results of the data analysis. This is done through explanations and analysis of socio-historical reflections and discursive analysis around the category and the realization of social rights. It is proposed to construct a concept that articulates all the categories that have been used, to explain it, among the aspects of contradiction, historicity, alienation and totality. The concept of guaranteeing the rights of children and adolescents permeates all this work, as it is established within a precise theoretical, political and ideological referential, that is, the Marxist dialectic. This apprehension of the concept is based on a critical political formation, differentiated by reason of being a social process guided by a political culture, based on values that affirm democracy and human rights, from the processes of participation, organization and social policy. Finally, social policies and their variations on social protection, especially the rights of children and adolescents, are addressed, and this has repercussions in the media and in the mass society.